The Effect Of Crossword Puzzle Media On Writing Skills In Arabic Language Learning - Irsyad Hisyam Rakasiwi; Miatin Rachmawati (Universitas Cokroaminoto Palopo, 2024)
A common issue faced in efforts to improve Arabic writing skills is the lack of appropriate and engaging learning media models that can effectively facilitate the learning process while making it enjoyable for students. This study is a Pre-experimental study involving two classes as an experimental class and a control class using an experimental design